Evaluation of Maternal and Neonatal Outcomes in Pregnant Women with Placenta Previa and Placenta Accreta (Journal of Current and Advance Medical Research, 2022)
Background: Placenta praevia is a disorder that happens during pregnancy when the placenta is abnormally placed in the lower uterine segment, which at times covers the cervix. Placenta previa may be associated with placenta accreta (PA) or one of its more advanced forms as (placenta increta and percreta).Objective: The purpose of the present study was to evaluate the maternal and neonatal outcomes in patients with placenta previa and placenta accrete.Methodology: This prospective descriptive study was carried out at Different privet chamber in Dhaka City, during study period from January 2018 to December 2019. Among 75 cases (45 had placenta previa and 30 had placenta accrete) diagnosed preoperatively by ultrasound or postoperatively with or without PA. Maternal and neonatal outcomes were evaluated. All intraoperative and postoperative data were reported. The obtained data was analyzed by means of SPSS software (version 23.0) and p